Perlindungan Hukum Terhadap Kerugian Konsumen Atas Pemalsuan Merek Produk Beras - Lestari, Ismiyati Riri Puji; Sudiro, Amad (Universitas Ekasakti, 2023)
Consumer legal protection in Indonesia refers to legal efforts to protect consumers from various economic actions that harm them. This research uses normative legal research methods. The purpose of this study is to determine the law enforcement of legal protection of consumers for the purchase of rice products with fake brands. The results of this study indicate that riceoplosan is an effort to produce fake rice brands that endanger consumer health and is a criminal offense as stated in articles 254 to 259 of the Criminal Code. As an existence of legal protection by the state against this, business actors who counterfeit rice product brands can be subject to sanctions as in Article 62 of Law Number 8 of 1999 concerning Consumer Protection, namely a maximum penalty of 5 (five) years or a maximum fine of Rp.2,000,000,000.00 (two billion rupiah).